Propuesta de un plan de seguridad y salud para obras de construcción - Díaz Rojas, Nelson Armando (2010)
The present work provides criteria and tools for the elaboration and implementation of a safety and Health Plan for construction, showing a work of real construction Plan as an example of application.  The thesis takes as its reference the international management system of occupational safety and health OHSAS 18001, the Peruvian technical standards of safety and health in the construction such as the technical standard G.050 "Safety during construction" sector, "Standard basic of safety and hygiene in works of building" · R. S. 021-83 and the "regulation of safety and health in the work" D.S. 009-2005-tr, and is plasma in a plan concise and specific for the project "workshop for the repair of aircraft".  implementation of this plan is intended to meet the requirements set out in rules as mentioned and have a better control of safety and quality applied to the construction processes of the project, in order to achieve an impact pos...